Reperfusion and revascularization in acute myocardial infarction: [proceedings of the joint meeting of the Heidelberger Akademie der Wissenschaften and the International Society and Federation of Cardiology ..., Heidelberg , 15 - 17 September 1987] ; with 43 tables - Schettler, Gotthard; Jennings, Robert B.; Rapaport, Elliot; Wenger, Nanette K.; Bernhardt, Ralph (Springer, 1988)
Numerous new and important findings relating to the reconstruction of disturbed circulatory conditions in the coronary area are reported in this book. Fundamental aspects of therapeutic and prophylactic possibilities are covered in detail. Recommendations are then made to practitioners and clinicians for their everyday work. Critical standards for the indications and risks of the recommended procedures are given. Particular emphasis is laid on the possibilities for revascularization by means of dissolution of blood thrombi. The book aims to present top-level guidance to the pros and cons of reconstructive measures in coronary disorders
Keywords: Konferenzschrift -- 1987 -- Heidelberg; Koronarperfusion; Herzinfarkt; Revaskularisation